Escapism in Eugene O’Neill’s Long day’s Journey into Night - Haqi Ismaiel, Safaa; Salim Hammoudi, Zeena; Raheem Rahman Jaf, Susan (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
Long day's Journey into Night (Pulitzer Prize 1957) was Eugene O’Neill’s greatest autobiographical play in which he skillfully conveys through the members of his family a painful realistic portrait that reveals the strained familial relationships he experienced with his family during his youth. The play represents a day in the life of the Tyrones, which begins at 8:30 in the morning on James Tyrone's (the father) farm in August 1912 and ends in the last hours of the same day. It is a metaphorical, psychological, gradual, desperate journey that all the Tyrones take into the night (towards their personal problems) to explore the uttermost depth of familial relationship through their mutual accusations and blaming each other until they are separated by the darkness of their problems which isolate them from each other urging them to escape from their miserable and tragic reality by taking drugs, drinking and prostitutes. Escapism is one of the main themes of the play that is seen and justified by the depression, hostility and tension experienced by the four characters of the Tyrones family. They are unable to face their life's problems and they only get blame and mutual accusations from each other without the expected family attention and sympathy among them. The paper is an attempt to investigate the different motivations of the Tyrones for escaping from their bitter reality and the means used to do so.